1985
DOI: 10.1016/0169-4332(85)90214-4
|View full text |Cite
|
Sign up to set email alerts
|

AES and TDS studies of electrochemically oxidized Pt(100)

Abstract: Anodic films formed on Pt(lOO) in 0.3M HF using a quasi thin-layer electrochemical cell within a vacuum envelope were transferred to ultra-high vacuum for study by AtS and TDS. Films generated at potentials above 1.lV (RHE) survived emersion and pumpdown in a hydrated state. As the emersion potential increased, the lntegrated H 2 0 and 02 thermal desorption signals , also using stripping studies, concluded that, after surface adsorption started at D.8V, dermasorption (sorption into the first few layers of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

1987
1987
2007
2007

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…SUch a reversible oxygen species a s a s could have exciting implications for electrocatalysis. Although no oxygen was seen by Auger or thermal desorption on surfaces emersed at potentials just above this couple, this does not necessarily militate against an oxygen-type species since highly reversible species can spontaneously discharge in the electrolyte layer which remains on the surface upon emersion [14].…”
Section: Oxygen-like Speciesmentioning
confidence: 90%
See 3 more Smart Citations
“…SUch a reversible oxygen species a s a s could have exciting implications for electrocatalysis. Although no oxygen was seen by Auger or thermal desorption on surfaces emersed at potentials just above this couple, this does not necessarily militate against an oxygen-type species since highly reversible species can spontaneously discharge in the electrolyte layer which remains on the surface upon emersion [14].…”
Section: Oxygen-like Speciesmentioning
confidence: 90%
“…However, the electrode could be cycled through this peak many times with no discernible change in the vo1tam-metry. The lack of oxygen at lower potentials does not show that the 730 mV peak is not due to electrosorption of oxygen, since work on Pt(100) has shown that low coverages of electrosorbed oxygen do not survive emersion, evacuation, and transfer [14].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Using Auger spectroscopy [91], it has been observed that the anodic peak at ca. 1.2 V (peak (V)) originates from the oxidation of Pt (111), but the surface species corresponding to the highly reversible peaks at 0.75 V on Pt(111) could not be identified by this ex situ technique.…”
Section: General Features Of the Cathodization Process On Platinummentioning
confidence: 99%